Upregulation of choline acetyltransferase activity in hippocampus and frontal cortex of elderly subjects with mild cognitive impairment - DeKosky, Steven T.; Ikonomovic, Milos D.; Styren, Scot D.; Beckett, Laurel; Wisniewski, Stephen; Bennett, David A.; Cochran, Elizabeth J.; Kordower, Jeffrey H.; Mufson, Elliott J. (Annals of neurology, 2002)
In Alzheimer's disease (AD), loss of cortical and hippocampal choline acetyltransferase (ChAT) activity has been correlated with dementia severity and disease duration, and it forms the basis for current therapies. However, the extent to which reductions in ChAT activity are associated with early cognitive decline has not been well established. We quantified ChAT activity in the hippocampus and four cortical regions (superior frontal, inferior parietal, superior temporal, and anterior cingulate) of 58 individuals diagnosed with no cognitive impairment (NCI; n = 26; mean age 81.4 ± 7.3 years), mild cognitive impairment (MCI; n = 18; mean age 84.5 ± 5.7), or mild AD (n =14; mean age 86.3 ± 6.6). Inferior parietal cortex ChAT activity was also assessed in 12 subjects with end‐stage AD (mean age 81.4 ± 4.3 years) and compared to inferior parietal cortex ChAT levels of the other three groups. Only the end‐stage AD group had ChAT levels reduced below normal. In individuals with MCI and mild AD, ChAT activity was unchanged in the inferior parietal, superior temporal, and anterior cingulate cortices compared to NCI. In contrast, ChAT activity in the superior frontal cortex was significantly elevated above normal controls in MCI subjects, whereas the mild AD group was not different from NCI or MCI. Hippocampal ChAT activity was significantly higher in MCI subjects than in either NCI or AD. Our results suggest that cognitive deficits in MCI and early AD are not associated with the loss of ChAT and occur despite regionally specific upregulation. Thus, the earliest cognitive deficits in AD involve brain changes other than simply cholinergic system loss. Of importance, the cholinergic system is capable of compensatory responses during the early stage of dementia. The upregulation in frontal cortex and hippocampal ChAT activity could be an important factor in preventing the transition of MCI subjects to AD.